1987
DOI: 10.1017/s0950268800068023
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of respiratory viral infections by rapid immunofluorescence diagnosis, with emphasis on virus interference

Abstract: SUMMARYDuring the 7-year period from September 1978 to August 1985, smear specimens of nasopharyngeal secretions from 3132 patients mainly hospitalized children, taken in different regions in Norway, were examined for respiratory viruses by the rapid immunofluorescence (IF) technique. A positive diagnosis for respiratory syncytial virus (RSV), parainfluenza virus type 1, 2 and 3 or influenza A and B virus was made for 896 patients (29%). The greatest prevalence for all these viruses was observed during the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 22 publications
5
31
0
3
Order By: Relevance
“…The seasonal distribution of PIV1 and PIV2 cases in the 2 study years exhibited the curious biannual autumn periodicity in odd-numbered years [33] previously noted in the United States and Norway, although not in Finland [1,8,11,30]. In addition, the all-year-round occurrence of PIV3 cases with a slight predominance in the spring is also consistent with previous reports [30].…”
Section: Parainfluenza Virusessupporting
confidence: 89%
“…The seasonal distribution of PIV1 and PIV2 cases in the 2 study years exhibited the curious biannual autumn periodicity in odd-numbered years [33] previously noted in the United States and Norway, although not in Finland [1,8,11,30]. In addition, the all-year-round occurrence of PIV3 cases with a slight predominance in the spring is also consistent with previous reports [30].…”
Section: Parainfluenza Virusessupporting
confidence: 89%
“…Localized surveys of children with acute respiratory infections have confirmed the patterns described here for the parainfluenza and RS viruses (Buchan, Marten & Kennedy, 1974;Martin, Gardner & McQuillin, 1978;Hope-Simpson, 1981). In Norway (Anestad, 1982(Anestad, , 1987) the variations in incidence of the parainfluenza and RS viruses are similar to ours, but the 'interference' noted between these viruses and influenza A virus has not been seen in our data. The changes in age described in this review suggest that periodicity is an important factor in determining the age distribution of certain infections; or perhaps the periodicity is partly dependent on the age distribution of susceptibles?…”
Section: Resurgent Epidemicssupporting
confidence: 88%
“…This finding was supported by Norwegian observations which showed that RSV and influenza virus outbreaks usually did not reach their epidemiological peaks during the same period [13]. Later studies have supported these findings [14,15]. It should, however, be mentioned that these observations are not unambiguous [16].…”
Section: The Virus Interference Hypothesis-an Old Ideasupporting
confidence: 55%
“…in vivo [14]. In addition to interferon, it is possible that other broadly reactive responses of the innate immune system may also contribute.…”
Section: The Virus Interference Hypothesis-an Old Ideamentioning
confidence: 99%